Eleocharis endounifascis: A new species of Eleocharis subgenus Limnochloa (Cyperaceae) from northern South America - Hinchliff, C. E.; Petersen, S.; Roalson, E. H. (Phytotaxa, 2013)
A new species, Eleocharis endounifascis, is described and illustrated. This species inhabits standing water in disturbed, open habitats, occurring among a mosaic of wet forest, and probably also flourishes in sunny, seasonally inundated wetlands from Belize to southeastern Venezuela and Guyana to Brazil. It was previously confused with Eleocharis interstincta in herbarium collections and floristic works.